Grapefruit Seed Extract Reduces Gastrointestinal Symptoms - Uehleke, Bernhard; Storr, Martin; Hörning, Martin (Zeitschrift für Phytotherapie, 2024)
In this explorative longitudinal survey, self-reported data was collected from persons suffering from chronic gastrointestinal symptoms, who were seeking relief employing self-medication with a grapefruit seed extract (GKE). This is not a clinical trial nor a non-interventional study, but an explorative longitudinal survey with self-reports. The data was collected online and there were no personal contacts with a physician or a study nurse. Participants followed their own decision to use GKE and to provide their data to a data retrieval system, following informed consent according to existing national regulations on data protection. The test product was provided by the sponsor to make sure that the correct product was used for the intended observation period.Drop in criteria were chronic gastrointestinal symptoms, including those of functional dyspepsia (FD, resp. non-ulcer dyspepsia NUD) and/or irritable bowel syndrome (IBS) for more than 4 weeks, resulting in a score of an expanded Nepean Index (‘total gastrointestinal score’) higher than 20. Symptoms were documented 4–12 days (VA) prior to GKE use on day 1 and then on day 1, days 28, 42 and 56 of continuous oral use. New symptoms, predominating symptoms, stool habits, amount of oral intake and global status was retrieved every day during the observation period. On day 56 some global assessments were additionally recorded.The evaluation cohort was intended to be at least 100, and within the survey cohort we were able to evaluate 100 subjects (15 m and 85 f). Total gastrointestinal symptom score decreased from a mean (±SD) of 78.7±36.9 points by 26.4% on day 14, by 53.1% on day 28, by 58.7% on day 42, and by 49.9% on day 56, when compared to day 1. Upper gastrointestinal symptoms like heartburn improved better compared to lower GI symptoms (by 57.9% versus 47.3% on day 56). Overall complaints were rated as “very strongly improved” by 30%, “strongly improved” by 42%, “somewhat improved” or “unchanged” by 20% and as “deteriorated” by 1%. GKE was tolerated well. Minor adverse events reported were judged as most probably unrelated by the authors. More than half of the participants rated the intake as “very pleasant” or “pleasant” and intended to continue GKE beyond the observation period.In this prospective uncontrolled survey, GKE seemed to improve GI-symptoms, based on users reports. These results need to be confirmed in controlled clinical trials proofing efficacy and tolerance of GKE in functional GI-diseases. Data collected from participants without any personal contact bear a high risk of bias. Evaluation of self-treatment as presented here is clearly restricted to marketed products and may report interesting details of self-treatment outside prescription settings.
Keywords: Gastrointestinal symptoms; dyspepsia; IBS; grapefruit; online-survey; herbal